Comparative Analysis of Localization Methods for Accurate and Robust Positioning - Ilnytskyi, Ivan (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Localization, the task of determining position in an environment, is fundamental for robotics, navigation, and tracking [1][2]. This paper reviews modern approaches with emphasis on mathematical and computational modeling. We compare geometric methods [6], dead-reckoning with sensor fusion [3][4], graph-based optimization (SLAM) [11][12], and deep learning techniques [5][8]. A comparative table highlights their accuracy, robustness, and main trade-offs. The review indicates that multi-sensor fusion and robust estimation improve reliability [3][4], while deep learning adds potential but requires large datasets and careful design [5]. Локалізація, тобто визначення положення в середовищі, є фундаментальною задачею для робототехніки, навігації та систем відстеження [1][2]. У статті розглянуто сучасні підходи з акцентом на математичне та обчислювальне моделювання. Порівнюються геометричні методи [6], одометрія з сенсорним злиттям [3][4], оптимізаційні підходи на основі графів (SLAM) [11][12] та методи глибинного навчання [5][8]. Порівняльна таблиця висвітлює їхню точність, надійність та основні компроміси. Огляд показує, що багатосенсорне злиття та стійкі методи оцінювання підвищують надійність [3][4], тоді як глибинне навчання є перспективним, але вимагає великих обсягів даних та ретельного проєктування [5].